КҮНХОЖА ШЫҒАРМАЛАРЫНДА ҚАРАҚАЛПАҚЛАРДЫҢ СОЦИАЛ ЭКОНОМИКАЛЫҚ АЎҲАЛЫ - Есназарова, З.Б. (SCIENCE and SOCIETY, 2021)
The article discusses the situation in the socio-economic life of Karakalpak in the XIX century on the example of the works of Karakalpak poet Kunkhodza. The life of the Karakalpak people, was analysed by historical events in the poems "Zhailau (My Valley)", "OLim (Death)", "Kun kaida" (when will come such day?), "Shopanlar (shepherds
Keywords: Zhandaryia; Turkistan; Dzungaria; Differentiation; Arys; Zhayik; Emba; Economic; Social